2020
DOI: 10.1016/j.heliyon.2020.e04920
|View full text |Cite
|
Sign up to set email alerts
|

Lactic fermentation of cereals aqueous mixture of oat and rice flours with and without glucose addition

Abstract: Studies of the ability of probiotics to ferment cereal flours are necessary to obtain products with enhanced nutritional value. In this study, Lactobacillus paracasei CBA-L74 was used to ferment cereal aqueous mixtures containing both oat (7.5% w/v) and rice flours (7.5% w/v), with and without glucose, to understand whether glucose addition could have any effect on growth and metabolism. Viability, pH, metabolites production during fermentation (24 h, 37 °C) and substrates reduction were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Most of these types of functional foods are dairy-based products [20][21][22], but products of a different nature are also on the rise. The ability of the bacterial strain that was used in the present study to ferment food matrices, such as cereals and legumes, has previously been demonstrated [17,[23][24][25][26][27][28][29], and its probiotic activity has also been confirmed in previous studies [30][31][32][33]; in the present work, its ability to ferment an industrial product, such as banana puree, was investigated. Banana, both as a fresh or processed fruit, is one of the most consumed fruit crops worldwide, starting from infancy.…”
Section: Discussionmentioning
confidence: 62%
“…Most of these types of functional foods are dairy-based products [20][21][22], but products of a different nature are also on the rise. The ability of the bacterial strain that was used in the present study to ferment food matrices, such as cereals and legumes, has previously been demonstrated [17,[23][24][25][26][27][28][29], and its probiotic activity has also been confirmed in previous studies [30][31][32][33]; in the present work, its ability to ferment an industrial product, such as banana puree, was investigated. Banana, both as a fresh or processed fruit, is one of the most consumed fruit crops worldwide, starting from infancy.…”
Section: Discussionmentioning
confidence: 62%
“…The purpose of this work was to verify whether fermentation was carried out on a suspension with higher solid content (52% w/v) than that used in the past (15% w/v) (Gallo, Nigro, Passannanti, Salameh, et al., 2019; Gallo, Passannanti, et al., 2019; Gallo et al., 2020) is possible. Assuming possible problems related to the prefermentation heat treatment on such a high solid content (the starch of the flour in fact undergoes gelation due to heat), the experiment was carried out both with and without enzymatic treatment with amylase.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the present work, the amylase pretreatment was applied to test the feasibility of fermenting a high solid content matrix (52% w/v wheat flour) to possibly reduce the drying times and relative cost. To note that in past experimentations, a percentage of 15% w/v of flour was used (Gallo, Nigro, Passannanti, Salameh, et al., 2019; Gallo, Passannanti, et al., 2019; Gallo et al., 2020). Fermentations were carried out with and without amylase pretreatment and the outcome was evaluated in terms of the ease of mixing and, consequently, suspension homogeneity, bacterial growth, and lactic acid production as well as the consumption of the substrates during the fermentation processes.…”
Section: Introductionmentioning
confidence: 99%
“…The fermenting strain used for this work was Lactobacillus paracasei (LP) CBA L74, and its probiotic nature was already demonstrated by in vivo studies [4]. Fermentation of cerealbased substrates using LP CBA L74 as a starter culture was widely studied in previous works for aqueous rice, oat, and wheat flour suspensions [5,6], and for aqueous mixtures of oat and rice flours [7], highlighting how the addition of different concentrations of glucose to the fermenting medium could affect bacterial growth and lactic acid production during the process.…”
Section: Introductionmentioning
confidence: 99%